Algoritma Dijkstra Dalam Pemetaan UMKM Deli Serdang Berbasis Android - Arta Deva Victoria, Talenta; Hermansyah, Hermansyah (Ali Institute of Research and Publication, 2023)
This study aims to implement Dijkstra's algorithm in mapping Micro, Small and Medium Enterprises (MSMEs) in the Deli Serdang area using the Android platform with Java language. This MSME mapping aims to provide information on the nearest MSME location to users by using a mobile-based Geographic Information System (GIS). This study uses a software development approach with quantitative and qualitative methods. MSME location data was collected through surveys and interviews with business owners. This data is then processed and analyzed using the SketchUp software to build a visual model of MSME locations in the Deli Serdang area. In addition, an Android-based mobile application was developed using the Java programming language to provide an interactive and easy-to-use interface. This application provides information on the location of UMKM as well as recommendations for the closest route from the user's location to the UMKM you want to visit. The results of the study show that Dijkstra's algorithm has succeeded in producing recommendations for the closest route and travel time to MSMEs, so this application can assist users in finding MSME locations quickly and accurately. Users can also view detailed information about each MSME, such as business descriptions, hours of operation, and contacts to contact. This application is expected to increase the accessibility of information for visitors and potential MSME consumers in the Deli Serdang area. In addition, it is hoped that it can help increase the competitiveness and promotion of MSMEs and provide support for local economic growth.